Characterization of mucoadhesive nasal gels containing midazolam hydrochloride prepared from Linum usitatissimum L. mucilage - Shyamoshree Basu; Amal Kumar Bandyopadhyay (Universidade de São Paulo, 2011)
Nasal drug delivery systems prepared from natural materials are gaining importance in the field of pharmaceutical technology. Mucilage isolated from Linum usitatissimum L. (LUM) seeds was reported to be an effective natural mucoadhesive agent. The present study deals with a comparison of various characteristics of nasal gels containing midazolam hydrochloride (HCl) prepared from mucoadhesive agent extracted from Linum usitatissimum L. seeds and synthetic polymers like HPMC and Carbopol 934P in terms of texture profile analysis, mucoadhesive strength, and in vivo drug absorption profiles. It was observed that gels formulated with the natural mucilage showed better results than the synthetic gels in all aspects like hardness, adhesiveness, cohesiveness and mucoadhesive strength. The absolute bioavailability of midazolam hydrochloride from the natural gel was 97.55% whereas that of synthetic gels was 57.33% and 76.81% respectively. Sistemas de liberação nasal preparados com produtos naturais estão ganhando importância no campo da tecnologia farmacêutica. A mucilagem isolada de sementes de Linum usitatissimum L. (LUM) mostrou-se agente mucoadesivo eficaz. O presente estudo trata da comparação de várias características de géis nasais contendo cloridrato de midazolam preparados com agente mucoadesivo extraído das sementes de Linum usitatissimum L. e com polímeros sintéticos, como HPMC e Carbopol 943P, com relação ao perfil de textura, força mucoadesiva e perfis de absorção do fármaco in vivo. Observou-se que os géis formulados com mucilagem natural apresentam melhores resultados do que os sintéticos em todos os aspectos, como dureza, adesão, coesão e força mucoadesiva. A biodisponibilidade absoluta do cloridrato de midazolam a partir do gel natural foi de 97,55%, enquanto que nos géis sintéticos foi de 57,33% e 76,81%, respectivamente.